The Newfoundland Fracking Protest: Climate Change Action Without Climate Change Arguments - Simon Jansen (The University of Alabama, 2021)
Anyone who has worked on climate change initiatives comes to a point where they ask themselves, "Why don't people care?" Why does it not rattle people into decisive action when they hear that the future of the planet is at stake? This article highlights action on climate change that occurred without climate change being the main motivation.